The Law of Trusts - Lewis, Browne C. (Open textbook library., 2013)
The use of testamentary trusts is becoming an important part of estate planning. As a result, students who want to make a living as probate attorneys will need to know how trusts fit into estate planning. In addition, bar examiners realize that it is important for students to have a basic knowledge of trust law. That realization will result in bar examination questions that test that knowledge. This book is designed for use as a supplementary text for a course on wills and trusts and the primary text in a seminar or course exploring the law of trusts.